Comparative Conformational Analysis Of Peptide T Analogs - Akverdieva, Gulnare; Godjayev, Niftali; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2009)
A series of peptide T analogs were investigated within the molecular mechanics framework. In order to determine the role of the aminoacid residues in spatial formation of peptide T the conformational peculiarities of the glycine-substituted analogs were investigated. The conformational profiles of some biologically tested analogs of this peptide were determined independently. The received data permit to assess the active form of this peptide. It is characterized by p-turn at the C-terminal physiologically active pentapeptide fragment of peptide molecule. The received results are important for the investigation of the structure-activity relationship and may be used at design of a rigid-molecule drug against HIV. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Peptide T Analogs; Conformational Analysis; Structure Activity Relationship; Immunodeficiency Virus Receptor; Hiv Infectivity; L-alanine; Binding; Pentapeptide; Ribonuclease; Inhibitor; Dynamics; Homology; GP120; Konformasyon Analizi; Yapı Aktivite İlişkisi; Bağışıklık Sistemi Bozucu Virüs Reseptörü; HIV Enfeksiyonu; Bağlayıcı; Ribonükleaz; Önleyici; Dinamik; Homoloji